2017
DOI: 10.1017/jfm.2017.852
|View full text |Cite
|
Sign up to set email alerts
|

Thermal transfer in Rayleigh–Bénard cell with smooth or rough boundaries

Abstract: Several Rayleigh-Bénard experiments in water are performed with smooth or rough boundaries. We present new thermal transfer measurements obtained with large roughness elements arranged in a square lattice. The data are compared to previous ones obtained with smaller elements in the same cell (Tisserand et al., 2011). Experiments in the same apparatus without roughness are fully presented, as reference results, to allow for comparison. In the rough case, several regimes of heat transfer are identified : one sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 34 publications
4
21
0
1
Order By: Relevance
“…Roughness of the horizontal plates is an obvious candidate to trigger boundary layer instabilities possibly leading to an enhancement of the heat flux (Ciliberto & Laroche 1999) and possibly to the socalled ultimate regime predicted by Kraichnan (Kraichnan 1962;Roche et al 2010). The wave-length and typical amplitude of our topography is however much larger than the typical roughness used in experiments (Rusaouën et al 2018). Note also that roughness does not always lead to a heat transfer enhancement (Zhang et al 2018).…”
Section: Effect Of the Topography On The Heat Fluxmentioning
confidence: 82%
“…Roughness of the horizontal plates is an obvious candidate to trigger boundary layer instabilities possibly leading to an enhancement of the heat flux (Ciliberto & Laroche 1999) and possibly to the socalled ultimate regime predicted by Kraichnan (Kraichnan 1962;Roche et al 2010). The wave-length and typical amplitude of our topography is however much larger than the typical roughness used in experiments (Rusaouën et al 2018). Note also that roughness does not always lead to a heat transfer enhancement (Zhang et al 2018).…”
Section: Effect Of the Topography On The Heat Fluxmentioning
confidence: 82%
“…In regime III they found that these scaling exponents saturate to 0.30 to 0.50, respectively, with increasing λ. Rusaouën et al (2018) performed RB experiments with water in cylindrical containers for Ra up to 10 12 . They performed a set of measurements using smooth and rough plates with cubic roughness elements in a square lattice.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the use of rough plates disrupts the boundary layer structure and enhances the heat transport significantly, with γ 0.5 over some finite range of Rayleigh number. However, recent studies have shown that this effect is significant at moderate Rayleigh numbers only, while, for strong imposed temperature gradients and fixed geometry, the system settles back into the boundary layer controlled regime (16)(17)(18). Global rotation offers another way to alter the boundary layer dynamics and increase the exponent γ (19,20), albeit for an intermediate range of Ra only, and with a heat flux that is smaller than its nonrotating counterpart (21).…”
mentioning
confidence: 99%